Peningkatan Daya Saing Kualitas Lembaga Pendidikan melalui Fungsi-Fungsi Manajemen Sumber Daya Manusia - Zainal Abidin (JURNAL KAJIAN ISLAM MODERN, 2021)
An educational institution, to produce graduates who meet the specifications and targets set (quality standards), the human resources (SOM) involved in the learning and learning process must meet the requirements for work attitudes, knowledge and skills set. Therefore, the competitiveness and performance of an agency is largely determined by the quality of its SOM competence. The quality of SOM competence will ultimately affect the country's competitiveness to compete in the job market. On the other hand, an agency to be able to retain the best employees it has is not easy. To be able to retain employees, the management must be able to understand the needs of employees and be able to create a conducive work environment that can make employees feel motivated both internally and externally. This requires optimizing the role of the Human Resources Department (HRD). SOM is the key to win the global competition. The employment sector is a means to produce quality graduates who are ready to be competitive, produce quality graduates with their skills and knowledge, and provide excellent service with their attitude. Therefore, there needs to be a systematic and strategic effort in managing SOM.